Task Specific Focal Dystonia (Writer’s Cramp): An Unusual Adverse Effects of Aripiprazole - Priyajyoti Chakma; Punyadhar Das (Current Overview on Disease and Health Research Vol. 5, 2022)
Writer’s cramp is the most commonly identified tasks specific focal dystonia of writing, characterized by abnormal muscle spasm of hand and arm. In my case a 20(twenty) years unmarried male from urban part of Tripura, India was presented with history of difficulty to write because of a stiffening of his right hand and also he was noticed that prolonged period of writing caused cramping pain of his right hand. He was diagnosed a case of paranoid schizophrenia (F20.0) as per ICD-10 for last three years and was on tablet Aripiprazole. Diagnosis of writer’s cramp was made which developed after six months of treatment with Aripiprazole 15 mg.